Gambaran Faktor Risiko Kejadian Abortus Spontan pada Ibu Hamil di RSUD Panembahan Senopati Bantul Tahun 2017-2018 - Sari, Yollin Noviana; Herfanda, Esitra; Putri, Intan Mutiara (Poltekkes Kemenkes Padang, 2022)
Abortion is the release of fetus in the uterus before 20 weeks or less than 5 months of pregnancy and the fetus weights less than 500 gram. In addition, the fetus still cannot live outside the uterus. The risky factors of abortion are mother’s age, parity, previous abortion history, education, occupation, and the distance of pregnancy with the previous pregnancy. The study is to investigate the frequency distribution of risk factors of spontaneous abortion of pregnant women at Panembahan Senopati Regional Public Hospital of Panembahan Senopati Bantul in 2017 – 2018. The study was analytic in type. The population of the study was 60 pregnant women. The samples of the study were 54 pregnant women. The samples were taken using total population. The analysis method was univariat analysis to reveal frequency distribution. The study revealed that 54 people experienced spontaneous abortion and 40 people (74.1%) experienced imminens abortion and 14 people (25.9%) experienced incompletes abortion. The risk factors of spontaneous abortion based on univariat analysis were non-risky age, safe parity 91, 2, and 3), non - spontaneous abortion history, non- anemic condition, educational level of senior high school, working status, and more than 2 years of pregnancy distance. It is suggested that health officers perform midwifery care on pregnant women experiencing spontaneous abortion.